Numerical simulation of the creation of a fire fighting barrier using an explosion of a combustible charge - Dubinin, Dmytro; Korytchenko, Konstantin; Lisnyak, Andrei; Hrytsyna, Ihor; Trigub, Volodimir (Eastern-European Journal of Enterprise Technologies, 2017)
The problem of protection of forests from fire became particularly important in recent years. The use of fire barriers restricts propagation of fire through vegetation. The establishment of fire barriers occurs nowadays due to the use of condensed explosives substances. The study considers the establishment of fire barriers produced by an explosion of double combustion charges. A combustion charge is a polyethylene membrane filled with a fuel-air mixture consisting of combustible gas and air. An increase in the efficiency of a shock wave occurs when we use combustion charges, due to increased pressure pulse, which makes possible to increase the width of a fire barrier to 8 m. People can stow created combustion charges safely and they are much easier than condense charges due to the specific heat of combustion hydrocarbon fuels increased in several times. We conducted numerous studies to establish fire barriers by the explosion of double combustion charges. We established that purification of ground combustible material occurs at an excess pressure of about 1.2 atmospheres. We calculated fields of pressure, which arises in the explosion of combustion charges in a process of a numerical study. We determined the width of a fire barrier based on the analysis of maximum values of pressure reached at the front of a shock wave. We determined that the width of a fire barrier depends on a number of charges and energy of the explosion. They determine energy of the explosion. As a result of the study, we obtained the dependence of the width of a fire barrier on parameters of double charges. We substantiated the use of a double combustion charge in dependence on a type of vegetation